The Role of Realistic Threats to Prejudice against Ethnic Chinese in Indonesia - Audi Ahmad Rikardi (Universitas Islam Darul Ulum Lamongan, 2023)
Minority groups tend to be prejudiced by other groups, including Chinese Indonesian. Chinese Indonesians have massive power in Indonesia's economy and hence are considered a threat to occupation and housing opportunities. This study aims to understand realistic threats that would predict prejudice toward Chinese Indonesian. A quantitative method with a cross-sectional survey was conducted for data collection. Sample criteria include 18 years above and belonging to several ethnicities, Javanese, Sundanese, Maduranese, Bugis, Minangkabau, Malayan, and Batavian. Two hundred forty-one respondents participated in this study. This study found realistic threat predicted prejudice toward Chinese Indonesian. Realistic threat explains 18% prejudice toward Chinese Indonesian. Practical and theoretical implications were discussed further.